Postoperative Hemolytic Uremic Syndrome with Renal Cortical Necrosis Following Laparoscopic Hemicolectomy. (June 2013) - Lee, Jae-Won; Won, Nam Hee; Cho, Eunjung; Kim, Myung-Gyu; Jo, Sang-Kyung; Cho, Won Yong; Kim, Hyoung Kyu
<x xml:space="preserve">Abstract</x> Non-Shiga-like toxin-producing Escherichia coli (STEC) or atypical hemolytic uremic syndrome (aHUS) is observed in 5–10% of all hemolytic uremic syndrome (HUS) cases, and usually develops secondary to infections, malignancies, drugs, transplantation, pregnancy, and autoimmune disease. However, there has been no report on adult onset HUS initiated by surgical procedures except transplantation. We report a 66-year-old woman who incurred renal impairment on the first day after laparoscopic hemicolectomy. Hemolytic anemia, thrombocytopenia, absence of Shiga toxin associated disease, normal ADAMTS13 activity, and low serum C3 (not C4) were consistent with a diagnosis of aHUS. We performed plasma exchange with fresh frozen plasma. Nevertheless, deteriorated renal function was not recovered after the treatment. Although it is an uncommon postoperative complication, aHUS needs to be considered as a possible cause of acute kidney injury combined with thrombocytopenia and anemia after surgical procedures, considering its different treatment modality and poor outcomes.